Calcium Bioavailability from Diets Based on White Cheese Containing Probiotics or Synbiotics in Short-Time Study in Rats - Klobukowski, Jan; Modzelewska-Kapitula, Monika; Kornacki, Kazimierz (Pakistan Journal of Nutrition, 2009)
One of the postulated effects of pro- and prebiotics is their beneficial influence on mineral absorption from a diet. In the present study, calcium absorption from diets containing white cheese with the potentially probiotic Lactobacillus plantarum strain with a prebiotic addition such as inulin HPX (high performance for high temperature processes) and maltodextrin was investigated. 2.5% of each prebiotic was added to the cheese preparation. The bioavailability of minerals was expressed as apparent absorption and retention indexes. The highest calcium absorption (mg 5 day-1) was noted in group receiving probiotic cheese, however there was no significant difference between this and the group receiving control diet without pro- and prebiotics. Maltodextrin addition to the diet caused a negative effect on Ca balance. Both, apparent absorption (%, mg 5 days-1) and retention (mg 5 days-1) indexes in this group were significantly lower (P < 0.05) compared to other groups. The apparent retention (mg 5 days-1) of calcium was significantly higher (P < 0.05) in rats receiving probiotic cheese. Feeding rats with probiotic cheese, containing Lactobacillus plantarum strain, resulted in increased calcium retention compared to control and synbiotic diets.